2022
DOI: 10.3390/su14127513
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Economics and the SDGs: A Review of Their Relationships and Barriers

Abstract: Recently, environmental issues have increased, whereas the Earth’s natural resources have deteriorated. These problems have forced people and companies to engage in environmental economics to achieve sustainability. However, several barriers have been identified in the implementation of environmental economics. This literature review provides insights into environmental economics and the sustainable development goals (SDGs), as well as the correlation between these two subjects in general. Thus, information ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Implementing sustainable economic development strategies faces various challenges across different contexts. These challenges include barriers such as inadequate funding, technology, expertise, and awareness of the importance of sustainable economic activities (Setioningtyas et al, 2022). Additionally, challenges in sustainable development encompass the lack of clean energy, sustainable transport, natural resource management, public health, and sustainable production and consumption, which hinder the effectiveness of sustainable development (Alyami, 2019).…”
Section: Challenges Faced In Implementing Sustainable Economic Develo...mentioning
confidence: 99%
“…Implementing sustainable economic development strategies faces various challenges across different contexts. These challenges include barriers such as inadequate funding, technology, expertise, and awareness of the importance of sustainable economic activities (Setioningtyas et al, 2022). Additionally, challenges in sustainable development encompass the lack of clean energy, sustainable transport, natural resource management, public health, and sustainable production and consumption, which hinder the effectiveness of sustainable development (Alyami, 2019).…”
Section: Challenges Faced In Implementing Sustainable Economic Develo...mentioning
confidence: 99%
“…The UN highlights sanitation as an ideal indicator for the progress of human well-being, however, it is still a key issue around the world that has caused many diseases and raised mortality rates (Adhikari & Halden, 2022). In addition to it, water pollution causes about 2 million human deaths by year (Setioningtyas et al, 2022). Furthermore, Castañeda Camey et al (2020 found an association between water availability and gender issues, considering that, in Kenya, a strategy often used to reduce families' economic stress is the marriage of child daughters.…”
Section: Figure 3 Abstract Co-occurrence Networkmentioning
confidence: 99%
“…To sum up, startups can be described as a subgroup of SMEs-young, innovative companies addressing global markets based on technological, process or business model innovation [43,48,50,51]. They differ from large companies in terms of their organizational structure, leadership style, reactions to the environment, available resources and the internal context in which they operate [52,53] especially due to the fact that startup companies lack expertise, resources, funding, and technology [54]. In today's knowledge-based economy, innovation is seen as the driving force of the economy.…”
Section: Resilience With a Focus On Startup Companiesmentioning
confidence: 99%